Sistem Informasi Penagihan Pajak Menggunakan WhatsApp Gateway di Badan Pendapatan Daerah (BAPENDA) Kabupaten Pandeglang Berbasis Web - Siti Selfina Selfina; Sri Setiyowati; Andrianto Heriwibowo (Admin Situstika, 2024)
The problem that exists in the Regional Revenue Agency (BAPENDA) of Pandeglang Regency in carrying out the collection or collection of swallow's nest and billboard taxes to taxpayers still uses a manual process by sending an Annual Return (SPT) to each taxpayer. Through certain expeditions Thus, in collecting building land tax it is felt less efficient. The purpose of this study is to Build a Tax Deferral Information System Using WhatsApp Gateway in order to Increase Revenue Realization at the Web-Based Pandeglang Regional Revenue Agency (BAPENDA) to facilitate tax collection in Bapenda Pandeglang. This system is designed using structured design including: Flow Of System (FOS), Contex Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), normalization, database file structure, data dictionary design, input / output design, for system testing using black boxes and using Sublime Text Tools as Text Editor languages ( PHP, HTML, CSS and Java Script) and Database using MYSQL.The forms generated in the tax collection information system include: taxpayer forms, billboard tax forms, swallow tax letter forms and reports generated in the form of regional tax returns (STPD) and reprimand letters and information with Whatsapp Gateway.The system development method used is the SDLC (Software Development Life Cycle) method. The results of this study resulted in a WhatsApp Gateway-based billing system that can facilitate the collection of billboard and swallow's nest taxes at the Regional Revenue Agency of Pandeglang Regency